Wnt-mediated down-regulation of Sp1 target genes by a transcriptional repressor Sp5 - Fujimura, Naoko; Vacik, Tomas; Machon, Ondrej; Vlcek, Cestmir; Scalabrin, Simone; Speth, Martin; Diep, Dzung; Krauss, Stefan; Kozmik, Zbynek (The Journal of biological chemistry, 2007)
Wnt/beta-catenin signaling regulates many processes during vertebrate development. To study transcriptional targets of canonical Wnt signaling, we used the conditional Cre/loxP system in mouse to ectopically activate beta-catenin during central nervous system development. We show that the activation of Wnt/beta-catenin signaling in the embryonic mouse telencephalon results in the up-regulation of Sp5 gene, which encodes a member of the Sp1 transcription factor family. A proximal promoter of Sp5 gene is highly evolutionarily conserved and contains five TCF/LEF binding sites that mediate direct regulation of Sp5 expression by canonical Wnt signaling. We provide evidence that Sp5 works as a transcriptional repressor and has three independent repressor domains, called R1, R2, and R3, respectively. Furthermore, we show that the repression activity of R1 domain is mediated through direct interaction with a transcriptional corepressor mSin3a. Finally, our data strongly suggest that Sp5 has the same DNA binding specificity as Sp1 and represses Sp1 target genes such as p21. We conclude that Sp5 transcription factor mediates the downstream responses to Wnt/beta-catenin signaling by directly repressing Sp1 target genes.
Keywords: genetická transkripce; signální transdukce; Signal Transduction; Humans; Promoter Regions, Genetic; proteiny Wnt; Mice, Transgenic; beta-katenin; Down-Regulation; Molecular Sequence Data; Transcription Factors; Transcription, Genetic; molekulární sekvence - údaje; Sin3 Histone Deacetylase and Corepressor Complex; myši transgenní; konzervovaná sekvence; Wnt Proteins; lidé; zvířata; histondeacetylasa Sin3 a korepresorový komplex; reportérové geny; myši; represorové proteiny; myši inbrední C57BL; down regulace; Mice; buněčné linie; Amino Acid Sequence; Conserved Sequence; Repressor Proteins; Sp1 Transcription Factor; Cell Line; Genes, Reporter; Mice, Inbred C57BL; beta Catenin; transkripční faktory; Animals; transkripční faktor Sp1; terciární struktura proteinů; Protein Structure, Tertiary; promotorové oblasti (genetika); sekvence aminokyselin